(untitled) (Journal of Bangladesh Academy of Sciences, 2017)
In this paper, we introduce two notions of T2 property in fuzzy topological spaces by using quasi-coincidence sense and we establish relationship among our and other such notions. We also show that all these notions satisfy good extension property. Also hereditary, productive and projective properties are satisfied by these notions. We observe that all these concepts are preserved under one-one, onto, fuzzy open and fuzzy continuous mappings. Finally, we discuss initial and final fuzzy topologies on our second notion. Journal of Bangladesh Academy of Sciences, Vol. 41, No. 1, 47-56, 2017